A Novel Framework to Protect Animal Data in a World of Ecosurveillance. (29th April 2020) - Lennox, Robert J; Harcourt, Robert; Bennett, Joseph R; Davies, Alasdair; Ford, Adam T; Frey, Remo M; Hayward, Matt W; Hussey, Nigel E; Iverson, Sara J; Kays, Roland; Kessel, Steven T; Mcmahon, Clive; et al.
Abstract: Surveillance of animal movements using electronic tags (i.e., biotelemetry) has emerged as an essential tool for both basic and applied ecological research and monitoring. Advances in animal tracking are occurring simultaneously with changes to technology, in an evolving global scientific culture that increasingly promotes data sharing and transparency. However, there is a risk that misuse of biotelemetry data could increase the vulnerability of animals to human disturbance or exploitation. For the most part, telemetry data security is not a danger to animals or their ecosystems, but for some high-risk cases, as with species' with high economic value or at-risk populations, available knowledge of their movements may promote active disturbance or worse, potential poaching. We suggest that when designing animal tracking studies it is incumbent on scientists to consider the vulnerability of their study animals to risks arising from the implementation of the proposed program, and to take preventative measures.